AN ANALYSIS OF INTERJECTION EXPRESSION FOUND IN DIGITAL COMMUNICATION VIEWED PRAGMATIC PERSPECTIVE - Nike Aulia Andhini; Yuliyanto Sabat; Siti Aisyah (IKIP Siliwangi, 2024)
Interjection was an important part of language used to express feelings or emotions under any circumstances. In Digital communication, interjections were often used to express feelings quickly and efficiently. The purpose of this research was to describe the expression of interjections in digital communication. This research used qualitative research. The method used in this research was the descriptive method. Digital communication, WhatsApp user was the subject of this investigation in WhatsApp Group. The object of the research was the text used in conversations within the WhatsApp group.The findings contained 6 type interjections from 12 data. There were Interjection of Annoyance, Interjection Admiration or Satisfaction, Interjection of Gratitude, Interjection of Hope, Interjection of Surprise, and Interjection of Call which were found as a consequence of the research. Annoyance was the most frequently used interjection.